NEGOTIATING THE IDENTITY OF THE VILLAGE RUWAH TRADITION IN MOJORUNTUT VILLAGE AS LOCAL WISDOM - Avrilia Herista, Nasya; Kukuh Sinduwiatmo (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The problem raised in this study is how identity negotiations take place in the implementation of Ruwah Desa and how the community interprets this tradition in the modern era. This research aims to reveal the role of Ruwah Desa in preserving local wisdom as well as a strategy to strengthen the community's cultural identity. Method: The research method used is qualitative descriptive with a phenomenological approach, with the research subject of the Mojoruntut Village community and the research object in the form of identity negotiation practices in the Ruwah Village tradition. Data was obtained through interviews, observations, and documentation of five key informants, including religious leaders, village officials, community leaders, youth organization leaders, and local residents. Results: The results of the study show that identity negotiation in the Ruwah Desa tradition takes place through four stages, namely the formation of individual identity through direct involvement in ritual processions, maintaining traditions collectively as cultural heritage, identity change through the reinterpretation of the younger generation that emphasizes socio-cultural aspects, and interaction in the modern era through the use of social media for cultural documentation and promotion. Novelty: The Ruwah Village tradition in Mojoruntut Village, Krembung District, Sidoarjo Regency, is a form of local wisdom that still exists in the midst of globalization and modernization. This tradition is not only interpreted as a tribute to ancestors, but also serves as a space for negotiating community identity in strengthening social solidarity, the value of mutual cooperation, and spiritual connection with the surrounding environment. In conclusion, the Village Ruwah Tradition is a dynamic and adaptive tradition, able to maintain the essence of local wisdom values while adapting to the times, so that it remains relevant as a support for the cultural identity of the Mojoruntut community.